Telaah Atas Teori-teori Pemberlakuan Hukum Islam Di Indonesia - Ahmad Badrut Tamam (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2017)
Islamic law has long lived in the legal consciousness of Islamic society in Indonesia along with the growth and development of Islam. This can be traced back to the early days of Islam entering Indonesia. But since the arrival of the colonial, Islamic law experienced-ups and downs. The enactment of Islamic law in Indonesia at this time is often not based solely on what actually takes place in society, but rather shows its form as a result of social construction created by colonialists, with a view to achieving certain goals. As an antithesis of the colonial policy, there arose various theories of the enforcement of Islamic law initiated by some Nation children, of course the theories are more objective and far from the political interests, although it is undeniable that the emergence of some of the theories initially aimed to oppose policy - colonial policy. Post-independence, the enforcement of Islamic law in Indonesia has found mementumnya and along with the times, several theories of the enforcement of Islamic law was emerging.